Share repurchases and firm performance: new evidence on the agency costs of free cash flow - Nohel, T (Journal of Financial Economics, 1998)
In this paper we examine tender offer share repurchases to differentiate between the information signaling and free cash flow hypotheses. Previous work in this area has focused on announcement period returns. While we also examine announcement returns, our primary emphasis is on operating performance changes surrounding repurchases. We argue that the information contained in changes in operating performance, and its determinants, enables us to differentiate between the two hypotheses. Our primary finding is that operating performance following repurchases improves only in low-growth firms, and that these gains are generated by more efficient utilization of assets, and asset sales, rather than improved growth opportunities. Thus, repurchases do not appear to be pure financial transactions meant to change the firm's capital structure but are part of a restructuring package meant to shrink the assets of the firm. This evidence leads us to conclude that the positive investor reaction to repurchases is best explained by the free cash flow hypothesis.